Flash Fiction of the Latin/o Americas: Another Approach - Aldama, Frederick (Revista Ciencia y Cultura, 2013)
This essay focuses on how a select few flash fictions are built by Latino authors and consumed by readers (Latino and otherwise) who share a common, deep ancestral evolution that has led to the growing of some fundamental cognitive and emotive biological mechanisms. It therefore turns to the insights offered by the research in the brain sciences and cognitive developmental psychology as well as to a specific analysis of several U. S. Latino flash fictions. In each flash fiction we shall see how these authors use language, narrative technique, and imagination to give in a few brushstrokes a representation of the full range of human emotions, moral dilemmas, and cognitive capabilities. Aldama opens the essay with the discussion of Monterroso's El dinosaurio as a primer of sorts to indicate what happens when readers encounter Latino narrative fiction generally and Latino short short fiction (flash fiction) specifically. While he focuses on the flash fiction created by U.S. Latinos, much of what he discusses below can reveal much about what readers do generally when they encounter narrative fiction. This could be seen in the short short format other than Latino flash fictions such as those from China known as "smoke-long stories" or from Japan known as "palm-of-the-hand stories". But it also applies more globally to any and all kinds of narrative fiction -novels, comic books, and films and from all over the planet. That is, the exploration of Latino authored flash fiction can and does reveal much about how such all variety of narrative fiction blueprints trigger and then guide a complex array of our mind/brain's sense-making faculties.